EFFECTS OF DIFFERENT MINERAL INCLUSIONS IN ANCHOVY BYPRODUCT BASED FEEDS ON GROWTH PERFORMANCE OF RED CLAW CRAYFISH, Cherax quadricarinatus - JAMIL, MUHAMMAD KHAIRUL ASHRAF; SHAPAWI, ROSSITA; YONG, ANNITA SEOK KIAN; LIM , LEONG SENG; TUZAN, AUDREY DANING; ABD HALID, NUR FATIHAH (Malaysian Applied Biology, 2022)
The purpose of this study was to evaluate the effects of different mineral inclusion in anchovy by-product (ABP) based feeds on the growth performance of red claw crayfish juveniles, Cherax quadricarinatus. A total of five experimental feeds with the inclusion of different mineral levels from 0-2.0% of the diet (M0, M0.5, M1.0, M1.5, & M2.0%) were fed to triplicate groups of 12 juvenile red claw crayfish with an average initial body weight of 2.20±0.10 g. There was no significant difference in terms of final body weight (g), final length (cm), weight gain (%), length gain (%), specific growth rate (%/d), and survival rate (%) of the juvenile red claw crayfish at the end of the feeding trial. Feed conversion ratio ranged from 1.60 (M0.5) to 1.76 (M1.0). Similar to the growth performance, the molting frequency was not affected by the different mineral inclusions in the feeds. Mineral inclusion in the feeds based on ABP can be reduced up to 0%, at least in a short culture period, and higher possibility of including minerals less than 2% in the feeds for juvenile red claw crayfish in a long-term culture period. Considering the good growth and survival of juvenile red claw crayfish in all treatments, the use of ABP as a source of protein and mineral in feeds for juvenile red claw crayfish is highly recommended as this will reduce the feed cost due to the much lower price of ABP. It can be concluded that the anchovy by-product meal used in the present study is a high potential ingredient to supply dietary protein and minerals in the formulated feeds for juvenile red claw crayfish